English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Simplify the expression.

square root12b - square root48b + 5 Square root3b

2006-12-03 13:41:11 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

√12b - √48b + 5 √3b

2 √3b - 4√3b + 5√3b

3 √3b

2006-12-03 13:46:04 · answer #1 · answered by Anonymous · 0 1

√12b - √48b + 5 √3b
in the first expression, you can determine that √4 * √3 = √12, hence 2√3b; then, the largest perfect square 48 is divisible is √16*√3, therefore 4√3b, so you then have...

2 √3b - 4√3b + 5√3b
now, just perform the problem algebraically (note: only numbers with like square roots can be added and/or subtracted); therefore, you obtain

3 √3b as an answer

2006-12-03 21:51:56 · answer #2 · answered by Anonymous · 0 0

This is kind of similar to finding the common denominator so you can add and subtract fractions. You need everything under each sqrt sign to have the same value. The smallest base under a sqrt is 3b. So, you need to figure out how to make each of the other terms equal to 3b and then use the extraction of roots.

sqrt(4 * 3b) - sqrt(16 * 3b) +5sqrt(3b)

Separate the terms

sqrt(4) * sqrt(3b) - sqrt(16) * sqrt(3b) + 5sqrt(3b)

find the values of what you can

2sqrt(3b) - 4sqrt(3b) + 5sqrt(3b)

then just add and subtract like you would any other value.


Answer would be: 3sqrt(3b)

2006-12-03 21:51:06 · answer #3 · answered by antheia 4 · 0 0

sqr root (12b) - sqr root (48b) + sqr root (3b)
= sqr root (4*3*b) - sqr root (16*3*b) + 5*sqr root (3*b)
= sqr root (4) * sqr root (3b) - sqr root (16) * sqr root (3b) + 5 * sqr root (3b)
= 2 sqr root (3b) - 4 sqr root (3b) + 5 sqr root (3b)
= sqrroot(3b) * (2-4+5) [square root (3b) is one factor, and (2-4+5) another!]
= 3*sqrroot(3b)

you can leave it as it is, or present another way:
= 3 square root 3 * square root b

or work it out even further, like this:
= square root (3^2 * 3) * square root b
= square root (9*3) * square root b
= square root (27) * square root b
= square root (27b)

It all depends what your assignment, or teacher/professor requires

2006-12-03 21:55:02 · answer #4 · answered by Mirta G 2 · 0 0

sqrt(12b)=sqrt(4*3b) and sqrt(4)=2 so sqrt(12b)=2sqrt(3b)
sqrt(48b)=sqrt(16*3b) and sqrt(16)=4 so sqrt(48b)=4sqrt(3b)
5sqrt(3b) does not simplify
so since 2-4+5=3(adding the coefficients)
the answer is 3sqrt(3b)

2006-12-03 21:47:40 · answer #5 · answered by abc123zyx 2 · 0 0

sqrt(12b) = sqrt(4*3b) = 2sqrt(3b)
You can do the rest...

2006-12-03 21:45:03 · answer #6 · answered by Anonymous · 0 1

fedest.com, questions and answers